2001
DOI: 10.1016/s1010-7940(01)00982-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial revascularization in patients with severe ischemic left ventricular dysfunction. Long term follow-up in 141 patients

Abstract: In patients with left ventricular dysfunction, myocardial revascularization can be performed relatively safely with good medium term survival and improvement in quality of life and in left ventricular function. Coronary artery bypass graft may be offered to patients with impaired ventricular function, but careful patient selection and management when considering these patients for operation should assess potentially reversible dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
71
2
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 20 publications
12
71
2
7
Order By: Relevance
“…6,7) Recent studies have reported early postoperative mortality rates of 1.7%-11% in patients with LVD. 1,[6][7][8][9][10][11][12][13][14][15][16][17] The operative mortality rate in this study (2.5%) was similar to that reported in other studies, indicating the safety of the off-pump technique for patients with LVD.…”
Section: Discussionsupporting
confidence: 85%
“…6,7) Recent studies have reported early postoperative mortality rates of 1.7%-11% in patients with LVD. 1,[6][7][8][9][10][11][12][13][14][15][16][17] The operative mortality rate in this study (2.5%) was similar to that reported in other studies, indicating the safety of the off-pump technique for patients with LVD.…”
Section: Discussionsupporting
confidence: 85%
“…The operative mortality rate in patients undergoing CABG is associated with several risk factors as female gender, advanced age, obesity, severity of coronary artery disease, low cardiac index, preoperative cardiac failure etc 5,7,11 . Less invasive cardiac surgical procedures are gaining increased interest among the surgical community.…”
Section: Discussionmentioning
confidence: 99%
“…However, as many earlier and current studies demonstrate coronary artery bypass graft (CABG) procedure have improved long term survival in patients with impaired ventricular function [1][2][3][4][5][6] over the last fi fteen years. The benefi t is most obvious in patients with severe LV dysfunction with ejection fraction (EF) less then 35 % 1 and signs of myocardial viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Coronary artery bypass grafting with the use of the left internal mammary artery (LIMA) and vein grafts is the standard and widely accepted surgical approach in the treatment of coronary artery disease. 8 Vasospasm of the arterial grafts is a serious perioperative complication and may result in IMA hypoperfusion syndrome with its high mortality. 9 The reversibility of LV dysfunction depends on factors including the presence and extent of stunned and hibernating myocardium, the surgeon's ability to completely revascularize hibernating tissue, perioperative myocardial infarction and post-operative graft complication.…”
Section: Introductionmentioning
confidence: 99%